REPRESENTASI DINAMIS DAN KOLABORATIF MELALUI TATA LETAK DESAIN INTERIOR KANTOR TRAVELOKA DITINJAU DARI SEMIOTIKA PEIRCE - Dina Felpin Riwu, Emilia Nurul Fajar (Universitas Riau, 2019)
This study applies the theory of semiotics by Charles Sanders Peirce with the aim of knowing the signs that exist in the design of space in the office as well as for interior designer and architect practitioners to dissect and determine approaches that will serve as references in conceptualizing and designing office interior layouts. This study used a qualitative method. This qualitative study used the theory of semiotics by Charles Sanders Peirce by finding the signs seen in the interior design of the Traveloka office. Other sources of information such as literature and photos of Traveloka's office interior will be combined together using the data observation process. The findings of this study were to look at signs of dynamic and collaborative representation in the layout of the interior design of the Traveloka office located in every area and space, which uses a material with industrial concepts in interior elements. By finding the signs that existed in the interior design of the Traveloka office, it is expected that space users are sensitive to the concept of companies that want to portray the company's image through the design of office layouts.